Systemic-Immune-Inflammation Index as a Promising Biomarker for Predicting Perioperative Ischemic Stroke in Older Patients Who Underwent Non-cardiac Surgery - Zhang, Faqiang; Niu, Mu; Wang, Long; Liu, Yanhong; Shi, Likai; Cao, Jiangbei; Mi, Weidong; Ma, Yulong; Liu, Jing (Frontiers in Aging Neuroscience, 2022)
Objective: The aim of this study was to investigate the clinical prognostic values of the preoperative systemic-immune-inflammation index (SII) in elderly patients undergoing non-cardiac surgery, using perioperative ischemic stroke as the primary outcome. Methods: This was a large retrospective cohort study of elderly patients who underwent non-cardiac surgery between January 2008 to August 2019. The patients were divided into patients with SII < 583 group and patients with SII ≥ 583 group according to the optimal SII cutoff value. The outcome of interest was ischemic stroke within 30 days after surgery. Primary analysis, sensitivity analysis and subgroup analyses were successfully performed to confirm that the preoperative SII qualifies as a promising, independent prognostic indicator. Propensity score matching (PSM) analysis was applied to address the potential residual confounding effect of the covariates to further examine the robustness of our results. Results: Among the 40,670 included patients with a median age of 70 years (interquartile range [IQR]: 67, 74), 237 (0.58%) suffered from ischemic stroke within 30 days after surgery. SII ≥ 583 was associated with an increased risk of perioperative ischemic stroke by multivariate regression analysis (odds ratio [OR], 1.843; 95% confidence interval [CI], 1.369-2.480; P < 0.001). After PSM adjustment, all covariates were generally well balanced between the two groups. The correlation between the SII and perioperative ischemic stroke remained significantly robust (OR: 2.195; 95% CI: 1.574-3.106; P < 0.001) in PSM analysis. Conclusion: The preoperative SII, which includes neutrophil, platelet, and lymphocyte from routine blood analysis, was a potentially prognostic biomarker for predicting perioperative ischemic stroke after non-cardiac surgery in elderly patients. An elevated SII, which was derived from an optimal cutoff value of 583, was an independent risk factor for perioperative ischemic stroke.